2018
DOI: 10.1007/s11325-018-1662-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous positive airway pressure on cardiovascular biomarkers in patients with obstructive sleep apnea: a meta-analysis of randomized controlled trials

Abstract: Among patients with OSA, CPAP improves inflammatory marker hs-CRP, arterial stiffness marker AIx, and endothelial function marker FMD. These biomarkers may provide information related to response to treatment. Future studies will need to clarify the efficacy of these biomarkers in assessing cardiovascular risk reduction among OSA treated with CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
2
31
0
7
Order By: Relevance
“…However, our results cannot be directly compared to these previous RCTs because we enrolled only patients with RHT, a specific subgroup of the general hypertensive population with an a priori expected increased aortic stiffness and, hence, possibly a greater effect of CPAP on reducing it. Notwithstanding, we observed a very similar effect of CPAP on cf‐PWV (−0.40 m/s, 95% CI −0.82 to +0.02 m/s; p = .059) to the pooled meta‐analytic results previously noted (Ning et al, ). Most important, this effect was mainly due to preventing aortic stiffness worsening in the CPAP group, in contrast to the control group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, our results cannot be directly compared to these previous RCTs because we enrolled only patients with RHT, a specific subgroup of the general hypertensive population with an a priori expected increased aortic stiffness and, hence, possibly a greater effect of CPAP on reducing it. Notwithstanding, we observed a very similar effect of CPAP on cf‐PWV (−0.40 m/s, 95% CI −0.82 to +0.02 m/s; p = .059) to the pooled meta‐analytic results previously noted (Ning et al, ). Most important, this effect was mainly due to preventing aortic stiffness worsening in the CPAP group, in contrast to the control group.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanical properties of the arterial wall have a rather fixed, irreversible component determined by its load-bearing components, namely its elastin and collagen contents and to a lesser extent the matrix constituents, and also a dynamic component determined by vascular smooth muscle tone, which mainly depends on endothelium-dependent and independent factors, systemic and vascular inflammation, and the autonomic nervous system activity, as well as on the distending pressure itself (Phillips, Butlin, et al, 2013). We can speculate that patients with RHT, because of the long-standing bur- to arterial stiffness progression (Ning et al, 2019;Pépin, Tamisier, Baguet, & Lévy, 2013;Phillips, Butlin, et al, 2013;Ryan, 2013). These aspects might explain the somewhat modest effects of CPAP treatment on aortic stiffness in RHT patients observed in the present RCT, mainly limited to preventing its worsening, in contrast to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects are reversible by OSA treatment (i.e., CPAP) (Drager et al, 2007;Hui et al, 2012). In a meta-analysis (Ning et al, 2019) of 15 randomized controlled trials that assessed the efficacy of several biomarkers, subgroup analysis showed that CPAP was particularly effective in improving FMD in severe OSA patients and patients with effective CPAP use for ≥ 4 h/night. These findings support the cause and effect relationship between OSA and arteriosclerosis/atherosclerosis.…”
Section: Mechanisms Linking Osa and Arteriosclerosis/atherosclerosismentioning
confidence: 99%